Increase in seed tannin extractability and oxidation using a freeze-thaw treatment in cool-climate grown red (Vitis vinifera L.) cultivars. (5th March 2020) - VanderWeide, Joshua; Forte, Alessandro; Peterlunger, Enrico; Sivilotti, Paolo; Medina-Meza, Ilce G.; Falchi, Rachele; Rustioni, Laura; Sabbatini, Paolo
Highlights: The "freeze-thaw" treatment artificially induced seed darkening. Some cell vacuoles located between the cuticle and inner integument were disrupted. The change in seed color was highly correlated with the fraction of vacuolar tannins. Abstract: Grape seed maturation involves the gradual oxidation of tannins, decreasing excessive bitterness and astringency in wine. In cool climates, this process is limited by the short growing season, affecting wine quality. A "freeze-thaw" treatment on seeds of red vinifera cultivars at veraison and harvest was used to evaluate the effect of oxidation and extractability on seed phenolic fractions. Freezing increased the extraction of total phenolics and o- diphenols quantified from fractionation (fraction 1, vacuolar tannins; fraction 2, hydrogen bonded tannins; fraction 3, covalently bonded tannins), especially at harvest. Despite this, colorimetry, microscopy, oxidation reactivity index (ORI), and correlations between the color index and fractions indicated that freezing disrupted vacuole integrity, enhancing oxidation in the seed coat. In conclusion, vacuolar tannins (which are the main seed phenolics extracted during fermentation) were highly correlated with seed color change, potentially providing information for winemaking in cool climate regions.